Clinical utility of an epigenetic assay to detect occult prostate cancer in histopathologically negative biopsies: results of the MATLOC study - Stewart, Grant D; Van Neste, Leander; Delvenne, Philippe; Delrée, Paul; Delga, Agnès; McNeill, S Alan; O'Donnell, Marie; Clark, James; Van Criekinge, Wim; Bigley, Joseph; Harrison, David J (The Journal of urology, 2013)
Concern about possible false-negative prostate biopsy histopathology findings often leads to rebiopsy. A quantitative methylation specific polymerase chain reaction assay panel, including GSTP1, APC and RASSF1, could increase the sensitivity of detecting cancer over that of pathological review alone, leading to a high negative predictive value and a decrease in unnecessary repeat biopsies. The MATLOC study blindly tested archived prostate biopsy needle core tissue samples of 498 subjects from the United Kingdom and Belgium with histopathologically negative prostate biopsies, followed by positive (cases) or negative (controls) repeat biopsy within 30 months. Clinical performance of the epigenetic marker panel, emphasizing negative predictive value, was assessed and cross-validated. Multivariate logistic regression was used to evaluate all risk factors. The epigenetic assay performed on the first negative biopsies of this retrospective review cohort resulted in a negative predictive value of 90% (95% CI 87-93). In a multivariate model correcting for patient age, prostate specific antigen, digital rectal examination and first biopsy histopathological characteristics the epigenetic assay was a significant independent predictor of patient outcome (OR 3.17, 95% CI 1.81-5.53). A multiplex quantitative methylation specific polymerase chain reaction assay determining the methylation status of GSTP1, APC and RASSF1 was strongly associated with repeat biopsy outcome up to 30 months after initial negative biopsy in men with suspicion of prostate cancer. Adding this epigenetic assay could improve the prostate cancer diagnostic process and decrease unnecessary repeat biopsies.